KEPEMILIKAN MANAGERIAL, RISIKO INTERNAL DAN EKSTERNAL, EFISIENSI DAN NET INTEREST MARGIN (NIM) DI BURSA EFEK INDONESIA - Ardian Prima Putra (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to obtain empirical evidence of a number of factors that can affect the Bank's Net Interest Margin (NIM) on the Indonesia Stock Exchange (IDX) in 2010-2016. The factors that are thought to influence NIM in this study are managerial ownership, internal risk (non-performing loans (NPL)), external risk (inflation), and efficiency (operating expenses and operating income (BOPO)). This research is expected to be beneficial for bank shareholders in supervising and controlling bank management in managing NIM at the Bank, for management the bank can control the NIM at the bank, for the government to determine the bank's NIM policy appropriately, and for further research can add referrals in the field of banking research especially the NIM. This study uses multiple linear regression test, with the results simultaneously independent variables namely managerial ownership, non-performing loans, inflation, BOPO have a positive effect on Net interest Margin (NIM), while the partial test results (T-test) is variable NPL, inflation has a negative influence on the net interest margin (NIM) while the other variables do not have a bearing on the NIM. Keywords : Net Interest Margin, Managerial Ownership, Risk, Efficiency, IDX